(2). Consider the surface produced by the equation $xy^2z^3 = 2$ . Find the points in this surface closest to the origin?

So far here is what I have,


$$ f(x,y,z) = x^2 + y^2 + z^2 $$

Where f is the square of the distance from the point $(x,y,z)$ to the origin. We want to minimize $f$, so our constraint is

$$ g(x,y,z) = xy^2z^3 - 2 $$

We must solve

$$\nabla f = \lambda \nabla g \quad \text{ and } \quad g = 0$$

By the former we must have

$$ \Bigg( \begin{matrix} 2x \\ 2y \\ 2z \\ \end{matrix} \Bigg) = \lambda \Bigg( \begin{matrix} y^2z^3 \\ 2xyz^3 \\ 3xy^2z^2 \\ \end{matrix} \Bigg) $$ Solving this system we get equations

$$ 2x = \lambda \text{ } y^2z^3 $$ $$ $$ $$ 2y = 2\lambda \text{ } xyz^3 $$ $$ $$ $$ 2z = 3\lambda \text{ } xy^2z^2$$ $$ $$

This is where I start to get stuck. From what I gathered from websites and youtube videos is that I would try to solve it using either cases, or by having the left side equal the same thing. I tried the latter and believe the answers were

$$ y^2 = 2x^2 \to y = \pm x\sqrt(2) \text{ and}$$ $$ 2z^2 = 3y^2 \to z = \pm y \sqrt{\frac{3}{2}} $$

I got these solutions by multiplying the first, second, and third equation by yz, xz, xy, respectively. Then having the first equation equal the second and then having the second equation = third equation. So it should look like this:

$$ 2xyz_1 = \lambda \text{ } y^3z^4 $$ $$ $$ $$ 2xyz_2 = 2\lambda \text{ } x^2yz^4 $$ $$ $$

$$ 2xyz_3 = 3\lambda \text{ } x^2y^3z^2$$ $$ $$

But from here I am stuck and I have no idea what to do or even if I am on the right path. Any help would be greatly appreciated.



Note that $xyz\ne 0$ because if one is zero the other two must be zero. Thus we have that

$$\dfrac{2x}{y^2z^3}=\frac{2y}{2xyz^3}=\frac{2z}{3xy^2z^2}.$$ Simplifying the fractions we arrive at

$$\dfrac{2x}{y^2z^3}=\frac{1}{xz^3}=\frac{2}{3xy^2z}.$$ Now we cancel a $z$ in each denominator getting

$$\dfrac{2x}{y^2z^2}=\frac{1}{xz^2}=\frac{2}{3xy^2}.$$ From the first and the third we have $$6x^2y^2=2y^2z^2\implies z^2=3x^2.$$ From the second and the third $$3xy^2=2xz^2\implies 3y^2=2z^2\implies y^2=2x^2.$$ Thus

$$y=\pm\sqrt2 x,\quad z=\pm \sqrt 3 x.$$ Now use the constraint to get

$$\pm x\cdot 2x^2 \cdot 3\sqrt 3 x^2=2.$$

  • $\begingroup$ Thank you @mfl for your answer. I'm having trouble with some of the values in your fractions. I understand the first simplify, but I'm having trouble understanding the second and third. How do you get xz^2 and in the third simplify you don't have a z at all. $\endgroup$ – Hawaiian Rolls Dec 5 '16 at 1:33
  • $\begingroup$ After simplifying the fractions we have a $z$ in all denominators. So we can cancel it. $\endgroup$ – mfl Dec 5 '16 at 6:50

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.